2020
DOI: 10.1002/jtr.2421
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of happiness: Impact of the happiness level of a destination country on Chinese tourists' outbound travel choices

Abstract: This study examines the impact of the national happiness level of a country on Chinese tourists' travel choices using panel data of 113 countries from 2012 to 2017, controlling for other factors that contribute to Chinese outbound tourism. The results show that the happiness level of a destination country is positively and significantly associated with Chinese tourist arrivals in that country. Examination of the moderation effect reveals cultural distance plays an important role in the impact a destination's h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Several studies confirm that the general positive attitude of the native population, expressed, among other things, by the happiness index, attracts tourists to the region. Huang et al (2021) determined that a country's level of happiness affects its attractiveness to Chinese tourists, and the relationship is direct and significant between the level of happiness in a host destination and the number of Chinese tourists visiting it (case 113 countries for 2012-2017). Gholipour, Tajaddini & Foroughi (2022) proved that tourists spend more money in those countries where the level of happiness is higher when looking at a sample of 58 developed and developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies confirm that the general positive attitude of the native population, expressed, among other things, by the happiness index, attracts tourists to the region. Huang et al (2021) determined that a country's level of happiness affects its attractiveness to Chinese tourists, and the relationship is direct and significant between the level of happiness in a host destination and the number of Chinese tourists visiting it (case 113 countries for 2012-2017). Gholipour, Tajaddini & Foroughi (2022) proved that tourists spend more money in those countries where the level of happiness is higher when looking at a sample of 58 developed and developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research also found that Japanese advertisements had more fear and rules/formality cues due to their restraint, high level of uncertainty avoidance, and power-distance orientations [95]. Although Chinese culture can be classified as a restraint culture, the happiness levels of a destination country were positively and significantly associated with Chinese tourist arrivals in that country [96].…”
Section: Promotionmentioning
confidence: 99%
“…Fan also noted that the potential consumption power operated by state-owned travelling agencies of China and its authority regime may exert manipulation over the outflow of Chinese outbound tourists. Huang et al (2021) indicate that the happiness level of a destination country can cast numerous impacts on Chinese tourists' outbound travel choices, in which the authors indicate that Chinese outbound tourists' destination choices are, in its essence, casting impacts on destinations' happiness levels. Other corresponding measures include participating in international tourism conferences, setting up tourism offices in each other's territory, or conducting international tourism cooperation and exchanges.…”
Section: Chinese Outbound Tourism Diplomacy As Nation-state Powermentioning
confidence: 99%